Scientific journals: An approach to their classification, characteristics, and indexing systems in Latin America - Rivas Castillo, Cristian (2021)
In recent years, scientific journals have become the channel or medium through which researchers, academics, and society in general carry out the processes of dissemination and popularization of scientific knowledge, in this sense it is important to study this phenomenon. The objective of this article is to identify the theoretical background of scientific journals, as well as to conceptualize, classify and establish their characteristics, and to identify the indexing systems used by scientific journals in Latin America. The documentary analysis method was applied with a qualitative approach, non-experimental design, under a transversal descriptive level. After the documentary review, it was observed that; scientific journals are classified into electronic and printed journals where each one is classified according to different criteria such as periodicity, format, or publishing entity, on the other hand, evaluation criteria have been created that allow knowing the status of the journals, allowing them to enter in high impact databases. It is concluded that it is necessary that the editors and academic bodies in charge of the journals become aware of the importance of complying with the criteria for the evaluation of scientific activity to position the journals in high impact databases.